2011
DOI: 10.1590/s1676-06032011000100011
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização florística e estrutural de remanescentes florestais de Quedas do Iguaçu, Sudoeste do Paraná

Abstract: and structural characterization of forest remnants in Quedas do Iguaçu, Southeastern Paraná. Biota Neotrop. 11(1): http://www.biotaneotropica.org.br/v11n1/en/abstract?article+bn01911012011. Abstract:The Southwestern region of Paraná State is an area of great ecological relevance because it represents an ecotone between two important forest types of the Brazilian south-southeastern region: the Seasonal Semideciduous Forest (SSF) and the Araucaria Forest (AF). Despite its importance, there is a lack of floristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
1
8
0
6
Order By: Relevance
“…The distribution of species richness among families in the study area was similar to that found in other seasonal semideciduous forest studies in the Brazilian States of São Paulo (Cielo-Filho et al 2009, Souza et al 2012 and Paraná (Viani et al 2011, Gris 2012, Zama et al 2012, Rossetto & Vieira 2013; in the Province of Misiones, Argentina (Chediack 2008, Velazco et al 2015; and in the Departments of Canindeyú and Alto Paraná, Paraguay (Monge 2009). However, an interesting feature of the study area was the relatively low representativeness of Lauraceae and the relatively high richness of Solanaceae.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The distribution of species richness among families in the study area was similar to that found in other seasonal semideciduous forest studies in the Brazilian States of São Paulo (Cielo-Filho et al 2009, Souza et al 2012 and Paraná (Viani et al 2011, Gris 2012, Zama et al 2012, Rossetto & Vieira 2013; in the Province of Misiones, Argentina (Chediack 2008, Velazco et al 2015; and in the Departments of Canindeyú and Alto Paraná, Paraguay (Monge 2009). However, an interesting feature of the study area was the relatively low representativeness of Lauraceae and the relatively high richness of Solanaceae.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, the use of an inclusion criterion to sampling plant individuals -stem perimeter at breast height equal or more than 15 cm -by Gris (2012) and Souza (2015) (Viani et al 2011); in protected areas of the Argentine Province of Misiones: Iguazú National Park and its surroundings -72 species (Chediack 2008) and Osununú Private Reserve -96 species (Velazco et al 2015); in protected areas of the Paraguayan side of the area of influence of the Itaipu Lake -127 species (Monge 2009); and in the São Francisco State Park, northern Paraná State, where 113 tree species were recorded, although in this case the relatively low richness seems to be also related to the intensive practice of selective logging before the protected area had been established (Tomé et al 1999, Zama et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…A riqueza regional de táxons da flora da região sudoeste do estado do Paraná foi determinada por meio da compilação de dados disponíveis na literatura científica, literatura cinzenta e banco de dados online. Para tanto, recorreu-se aos trabalhos de Gorenstein et al (2010a;2010b), Viani et al (2011), Estevan et al (2011) e Neofloresta (2017), além dos registros oficiais das coletas botânicas já conservadas em herbários, incluindo dados incorporados no banco de dados online do Herbário Digital da Flora e Fungos do Instituto Nacional de Ciência e Tecnologia, dentro do Projeto Species Link do Centro de Referência em Informação Ambiental da Fundação de Amparo à Pesquisa do Estado de São Paulo (CRIA, 2013). Foram incluídos os grupos de plantas classificadas em angiospermas, gimnospermas e pteridófitas.…”
Section: Methodsunclassified
“…Dentre as fitofisionomias que compõem o bioma Mata Atlântica destacam-se nas regiões sul e sudeste do Brasil a Floresta Estacional Semidecidual e a Floresta Ombrofila Mista (Di Bitetti et al 2003, Viani et al 2011. Devido à grande expansão de perímetros urbanos, aumento de práticas agrícolas e industriais, atualmente esse bioma se restringe a pequenos remanescentes florestais que possuem grande importância ecológica, pois auxiliam na manutenção da diversidade biológica do local, além de contribuir para o bem estar da sociedade humana (Rylands & Pinto 1998, Bentes 2006.…”
Section: Introductionunclassified